Ultrasound and Doppler evaluation of salivary gland pathology - Patange, Neeraj A.; Phatak, Suresh V. (International Journal of Research in Medical Sciences, 2016)
Background: Lesions of salivary gland are very commonly encountered in clinical practice. Only by Clinical examination alone it is difficult to differentiate between them and know its exact cause and etiology. It would definitely benefit the patient as well as the doctor if they could get an idea of the exact type of lesion affecting the salivary gland. Hence, this study was undertaken to demonstrate as how high resolution ultrasound imaging and use of colour Doppler can be useful in evaluation of salivary gland lesions. Methods: Duration of study was1yearwith sample size of 30 patients. This study has been conducted in the department of Radiodiagnosis JNMC, Sawangi, Wardha all cases irrespective of age and sex referred to the department were evaluated. Aloka Prosound Alpha 7 USG machine with a high resolution probe linear transducer was used. The lesions were evaluated by high resolution real time ultrasound and colour Doppler. Results: Most of the patients were in the age group 41-50years and had male preponderance. Most presented with unilateral swelling which was tender and firm in consistency. Amongst the study group saladenitis was most frequent finding followed by pleomorphic adenoma and carcinoma. Pleomorphic adenoma was most common neoplasm having predilection for the parotid gland. Saladenitis was most common in submandibular gland. The commonest histopathological finding was pleomorphic adenoma. Conclusions: The study concludes that High resolution ultrasound can differentiate various salivary gland lesions. Addition with colour Doppler ultrasound can increase its diagnostic accuracy. High resolution ultrasound with colour Doppler sonography should be first line of imaging modality in suspected cases of salivary gland lesions.